Sagot :
Answer:
1.) 11
2.) 9
Step-by-step explanation:
For item #1:
[tex] \boxed{\begin{array}{c} \frac{s}{13}=\frac{22}{26} \\ \frac{s}{22} = \frac{1}{2} \\ \frac{\cancel{22} \cdot s}{\cancel{22}} = \frac{1 \cdot 22}{22} \\ \boxed{s = 11}\\ \end{array}}[/tex]
For item #2:
[tex] \boxed{\begin{array}{c} \frac{y - 5}{y + 3} = \frac{2}{6}\\ 6-30=2y+6\\ 6y\cancel{-30+30} = 2y+6+30\\ 6y=2y+36\\ 6y-2y=\cancel{2y} +36-\cancel{2y}\\ 4y=36\\\frac{\cancel{4y}}{\cancel{4}}=\frac{36}{4} \\\boxed{ y=9}\\\end{array}}[/tex]